The power of everyday politics : how Vietnamese peasants transformed national policy - Kerkvliet, Benedict J. (Cornell University Press, 2005)
Ordinary people's everyday political behavior can have a huge impact on national policy: that is the central conclusion of this book on Vietnam. In telling the story of collectivized agriculture in that country, Benedict J. Tria Kerkvliet uncovers a history of local resistance to national policy and gives a voice to the villagers who effected change. Not through open opposition but through their everyday political behavior, villagers individually and in small, unorganized groups undermined collective farming and frustrated authorities' efforts to correct the problems. The Power of Everyday Politics is an authoritative account, based on extensive research in Vietnam's National Archives and in the Red River Delta countryside, of the formation of collective farms in northern Vietnam in the late 1950s, their enlargement during wartime in the 1960s and 1970s, and their collapse in the 1980s. As Kerkvliet shows, the Vietnamese government eventually terminated the system, but not for ideological reasons. Rather, collectivization had become hopelessly compromised and was ultimately destroyed largely by the activities of villagers. Decollectivization began locally among villagers themselves; national policy merely followed. The power of everyday politics is not unique to Vietnam, Kerkvliet asserts. He advances a theory explaining how everyday activities that do not conform to the behavior required by authorities may carry considerable political weight.